Can accurate evaluation of the treatment success after radiofrequency ablation of liver tumors be achieved by visual inspection alone? Results of a blinded assessment with 38 interventional oncologists. (30th November 2020) - Laimer, Gregor; Schullian, Peter; Putzer, Daniel; Eberle, Gernot; Goldberg, S. Nahum; Bale, Reto
Abstract: Objectives: To assess the difficulties in the immediate judgment of treatment success after radiofrequency ablation (RFA) of liver tumors by visual inspection alone and to evaluate whether radiologist's expertise affects the resultant judgment. Methods: Peri-interventional CT-scans of nine patients with nine hepatocellular carcinomas with known outcomes after RFA were presented to 38 participants from 14 different countries. In a total of 342 reads, all interventional oncologists assessed the pre- and immediate post-interventional CT-scans through conventional side-by-side juxtapositioning of images and judged whether complete ablation (i.e., technical success and technique efficacy) was achieved. Results were compared regarding expertise in percutaneous tumor ablation (>50 interventions performed). An 'overcall' was defined as insufficient ablation that was misjudged as sufficient, and an 'undercall' as an erroneous assessment of complete ablation. Results: Overall 3.97 ± 1.27 out of 9 (44.1%) cases per radiologist were misjudged. The mean number of overcalls and undercalls per radiologist were 0.74 ± 0.50 out of 2 (37.0%), and 3.24 ± 1.28 out of 7 (46.3%), respectively. 18/38 (47.4%) participants had considerable experience in percutaneous tumor ablation, with such expertise having no significant influence on the results (overall: p = 0.70; overcalls: p = 0.87; undercalls: p = 0.75). Conclusions: Conventional side-by-side evaluation of treatment success after RFA of liver tumors by the juxtaposition of pre- and post-interventional CT-scans is very difficult for experienced radiologists. The implementation of advanced processing techniques such as rigid/non-rigid image fusion with the assessment of the periablational margin is thus likely needed in order to decrease errors and objectively evaluate technical success and predict technique efficacy of liver RFA.